The relative importance of COVID‐19 pandemic impacts on biodiversity conservation globally. Issue 1 (26th October 2021) - Gibbons, David W.; Sandbrook, Chris; Sutherland, William J.; Akter, Rezvin; Bradbury, Richard; Broad, Steven; Clements, Andy; Crick, Humphrey Q. P.; Elliott, Joanna; Gyeltshen, Ngawang; Heath, Melanie; Hughes, Jonathan; et al.
Abstract: The COVID‐19 pandemic has had an enormous impact on almost all aspects of human society and endeavor; the natural world and its conservation have not been spared. Through a process of expert consultation, we identified and categorized, into 19 themes and 70 subthemes, the ways in which biodiversity and its conservation have been or could be affected by the pandemic globally. Nearly 60% of the effects have been broadly negative. Subsequently, we created a compendium of all themes and subthemes, each with explanatory text, and in August 2020 a diverse group of experienced conservationists with expertise from across sectors and geographies assessed each subtheme for its likely impact on biodiversity conservation globally. The 9 subthemes ranked highest all have a negative impact. These were, in rank order, governments sidelining the environment during their economic recovery, reduced wildlife‐based tourism income, increased habitat destruction, reduced government funding, increased plastic and other solid waste pollution, weakening of nature‐friendly regulations and their enforcement, increased illegal harvest of wild animals, reduced philanthropy, and threats to survival of conservation organizations. In combination, these impacts present a worrying future of increased threats to biodiversity conservation but reduced capacity to counter them. The highest ranking positive impact, at 10, was the beneficial impact of wildlife‐trade restrictions. More optimistically, among impacts ranked 11‐20, 6 were positive and 4 were negative. We hope our assessment will draw attention to the impacts of the pandemic and, thus, improve the conservation community's ability to respond to such threats in the future. Abstract : Article impact statement : The COVID‐19 pandemic presents increased threats to biodiversity conservation globally yet reduced capacity to counter them. Resumen: La pandemia de COVID‐19 ha tenido un impacto enorme sobre casi todos los aspectos de la sociedad humana y sus proyectos; el mundo natural y su conservación no han sido la excepción. Por medio de un proceso de consultas a expertos, identificamos y categorizamos en 19 temas y 70 subtemas las maneras en las que la biodiversidad y su conservación han sido o podrían ser afectadas mundialmente por la pandemia. Casi el 60% de los efectos han sido claramente negativos. Posteriormente, creamos un compendio de todos los temas y subtemas, cada uno con textos explicativos, para que en agosto de 2020 un grupo diverso de conservacionistas experimentados con conocimiento de todos los sectores y geografías evaluara cada subtema de acuerdo con su probabilidad de impactar sobre la conservación de la biodiversidad en todo el mundo. Los nueve subtemas con la clasificación más alta tienen un impacto negativo. Estos temas son, en orden de clasificación: los gobiernos dejando de lado al ambiente durante su recuperación económica, reducción de los ingresos basados en el turismo de fauna, incremento en la destrucción de hábitat, financiamiento reducido del gobierno, aumento de la contaminación por plásticos y otros desechos sólidos, debilitamiento de las regulaciones en pro de la naturaleza y su aplicación, incremento en la captura ilegal de animales, disminución de la filantropía y amenazas para la supervivencia de las organizaciones de conservación. La combinación de estos impactos representa un futuro preocupante lleno de amenazas para la conservación de la biodiversidad y una capacidad reducida para contrarrestarlas. El impacto positivo con la clasificación más alta, el 10, fue el impacto benéfico de las restricciones en el mercado de fauna. De manera más optimista, entre los impactos clasificados de los lugares del 11 al 20, seis fueron positivos y cuatro fueron negativos. Esperamos que nuestra evaluación enfoque la atención hacia los impactos de la pandemia y así mejore la habilidad de la comunidad conservacionista para responder a tales amenazas en el futuro. Importancia Relativa de los Impactos de la Pandemia de COVID‐19 sobre la Conservación Mundial de la Biodiversidad